Changes in chemokines and their receptors in blood during treatment with the TNF inhibitor infliximab in patients with rheumatoid arthritis. (August 2013) - Eriksson, C; Rantapää-Dahlqvist, S; Sundqvist, KG
<x xml:space="preserve">Abstract</x> Objectives: Chemokines are involved in leucocyte recruitment into inflammatory sites. The release of certain chemokines is augmented by tumour necrosis factor (TNF). Infliximab, a monoclonal antibody that blocks the effects of TNF, is used for treatment of rheumatoid arthritis (RA). The effect of TNF blockage on chemokines is not fully understood. The aim of this study was to analyse the effects on chemokines and their receptors on peripheral mononuclear cells of anti-TNF treatment in RA patients. Method: Twelve patients with established RA who started treatment with infliximab and nine patients with early RA treated with other anti-rheumatic drugs were followed clinically for 30 weeks and chemokine levels in blood samples were analysed along with chemokine receptor expression on the surface of T cells and monocytes. Nine healthy subjects were included as a control group. Results: The chemokine CXCL10/IP-10 was significantly higher in RA patients than in healthy controls (p = 0.012). Two weeks after infliximab infusion, CXCL10/IP-10, CCL2/MCP-1, and CCL4/MIP-1β had decreased significantly (p = 0.005, 0.037, and 0.028, respectively), and after 30 weeks of treatment, soluble CD26 was significantly increased (p = 0.050). Several chemokine receptors on T cells were elevated in RA patients at inclusion. The expression of CCR2 and CXCR1 on T cells decreased significantly after infliximab treatment. Conclusions: The chemokines CXCL10/IP-10, CCL2/MCP-1, and CCL4/MIP-1β, mainly targeting the T-helper (Th)1 immune response, decreased after treatment with anti-TNF, suggesting a more pronounced effect on Th1 activity than on Th2-mediated response. Several chemokine receptors on blood T cells were elevated in RA patients, suggesting that they may be involved in the recruitment of T lymphocytes from the blood to affected tissues.